DARI MEMBACA KE MEMAHAMI:IMPLEMENTASI MODEL PEMBELAJARAN KOLABORASI DALAM MENINGKATKAN LITERASI DAN HASIL BELAJAR PESERTA DIDIK SEKOLAH DASAR - Melina Sufina; Dessy Dwitalia Sari; Muhsinah Annisa; Fathul Jannah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The problem in this research is that students experience difficulties in understanding reading texts, which impacts their low literacy comprehension and learning outcomes. In addition, students still experience difficulties in interpreting meanings, analyzing information, and expressing opinions logically and systematically. Therefore, learning innovation is needed through a combination of Problem Based Learning (PBL), Contextual Teaching Learning (CTL), and Cooperative Learning models aimed at describing teacher activities and analyzing improvements in literacy comprehension and learning outcomes of fourth-grade students at SDN Pasar Lama 1 Banjarmasin. This research employs a qualitative and quantitative approach using Classroom Action Research (PTK), conducted over four meetings in the 2024/2025 academic year. The research subjects consist of 29 students. Data were collected through observations of teacher activities, literacy comprehension, and learning outcomes, as well as written tests for quantitative data. Data analysis was performed using percentages and predetermined learning completion indicators. The results show that teacher activities in each meeting were carried out in the “Good” criteria and improved to a score of 27. Literacy comprehension increased from 41% in the “Less Complete” criteria in the first meeting to 93% in the fourth meeting. Students’ learning outcomes also improved to 100% in the final meeting. Based on these results, the combination of Problem Based Learning (PBL), Contextual Teaching Learning (CTL), and Cooperative Learning models effectively improves students’ literacy comprehension and learning outcomes. Keywords: literacy comprehension, learning outcomes, problem based learning, contextual teaching learning (ctl), cooperative learning